Association-Based Bilingual Word Alignment - Moore, Bob (Association for Computational Linguistics, 2005)
Bilingual word alignment forms the foundation of current work on statistical machine translation. Standard wordalignment methods involve the use of probabilistic generative models that are complex to implement and slow to train. In this paper we show that it is possible to approach the alignment accuracy of the standard models using algorithms that are much faster, and in some ways simpler, based on basic word-association statistics.